Emerging role of lncRNAs in osteoarthritis: An updated review - Wang, Rongliang; Shiu, Hoi Ting; Lee, Wayne Yuk Wai (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is a prevalent joint disease, which is associated with progressive articular cartilage loss, synovial inflammation, subchondral sclerosis and meniscus injury. The molecular mechanism underlying OA pathogenesis is multifactorial. Long non-coding RNAs (lncRNAs) are non-protein coding RNAs with length more than 200 nucleotides. They have various functions such as modulating transcription and protein activity, as well as forming endogenous small interfering RNAs (siRNAs) and microRNA (miRNA) sponges. Emerging evidence suggests that lncRNAs might be involved in the pathogenesis of OA which opens up a new avenue for the development of new biomarkers and therapeutic strategies. The purpose of this review is to summarize the current clinical and basic experiments related to lncRNAs and OA with focus on extensively studied H19, GAS5, MALAT1, XIST and HOTAIR. The potential translational value of these lncRNAs as therapeutic target for OA is also discussed.